HEALTH EFFECTS OF SECONDHANDSMOKE DURING PREGNANCY ON MATERNAL AND PERINATAL OUTCOMES IN TOMOHON CITY, NORTH SULAWESI, INDONESIA - Daichi Suzuki; Windy Mariane Virenia Wariki; Ishak Halim Octawijaya; Adrian Umboh; Erika Ota (The Indonesian Journal of Public Health, 2023)
Introduction: A study conducted in 31 countries described that over 60% of women and children are exposed to SHS outside. Aims: was to explore the association of secondhand smoke (SHS) exposure on maternal and perinatal outcomes in highland settings in Indonesia. Methods: The retrospective cross-sectional survey was used a random sampling method with 52-items of the questionnaire included information of women and infants. This study conducted with the community health center and all seven public health centers in Tomohon city, North Sulawesi, Indonesia, from May to October 2017. The participants were women who had given birth and were exposed to SHS during pregnancy. Their health condition was measured before and after pregnancy, the gestational week at birth, birth weight and height, and perinatal health conditions of the infants. Result: Among 234 women who completed the questionnaire and were included in the analysis. The 97% of household active smokers had a chance to smoke outside the house. Also, approximately 70% of women (162/234) reported exposure to SHS from active household smokers during pregnancy. Maternal secondhand smoke (SHS) exposure during pregnancy was significantly associated with the risk of reduction of birth weight (p = 0.02). Moreover, infants’ birth weight of mothers exposed to SHS outside the house was significantly less than those exposed to SHS only inside (p = 0.03).  Conclusion: Further research is required to focus on public smoke-free strategies to protect women and children’s health from SHS in Indonesia.